2009
DOI: 10.1159/000243714
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Injection with KCI: An Alternative Method in Selected Cases of Multifetal Pregnancy Reduction

Abstract: Multifetal pregnancy reduction (MFPR) offers a therapeutic option which reduces the maternal, prenatal, neonatal morbidity and mortality associated with multifetal pregnancies. In certain cases of MFPR, where difficulty is encountered in reaching the thorax due to the fetal position as well as the location of membranes and placenta, an alternative approach may be the insertion of the needle to the fetal cranium. We describe a new technique for MFPR performed by fetal intracranial injection of potassium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…There are a variety of methods by which to induce late TOP, which can include fetal intracardiac injection of other substances (such as a fibrin adhesive [13] or lidocaine [14]), other routes of injection (for example intracranial injection [15] or intraplacental injection of methotrexate [16]), intraumbilical air embolism [17], intra-amniotic digoxin [18], as well as surgical methods (such as radiofrequency ablation and cord occlusion). Whilst we do not expect significant differences in imaging features with different substances injected via an intracardiac route, this was not formally assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of methods by which to induce late TOP, which can include fetal intracardiac injection of other substances (such as a fibrin adhesive [13] or lidocaine [14]), other routes of injection (for example intracranial injection [15] or intraplacental injection of methotrexate [16]), intraumbilical air embolism [17], intra-amniotic digoxin [18], as well as surgical methods (such as radiofrequency ablation and cord occlusion). Whilst we do not expect significant differences in imaging features with different substances injected via an intracardiac route, this was not formally assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Presently, the preferred method for MFPR is a transabdominal intrathoracic or intracranial injection of potassium chloride (KCl). [6,7] Evidence suggests these methods are effective at 14 to 23 weeks of gestation for multifetal pregnancies derived from multiple eggs. [8] However, pregnancy loss rates of 7% to 9% for triplets and quadruplets and 42.9% for 6 or more fetuses following intrathoracic injection of KCl have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral blood supply was sufficient for KCl to enter the circulation quickly, leading to faster hyperkalemia and to fetal cardiac arrest. This mechanism, suggested by Lembet et al [9], is due to KCl directly getting into the arteries above the cranial tissues and entering the circulation. It is believed that intracranial puncture is more likely than other approaches to quickly enter the fetal circulation since these authors observed no fetal heart arrhythmia when the needle was introduced [9].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism, suggested by Lembet et al [9], is due to KCl directly getting into the arteries above the cranial tissues and entering the circulation. It is believed that intracranial puncture is more likely than other approaches to quickly enter the fetal circulation since these authors observed no fetal heart arrhythmia when the needle was introduced [9]. Observations for fetal cardiac arrest should continue for 20 min after injection to make sure the reduction is completed [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation